2009
DOI: 10.1136/bmj.b1374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of point of care testing for C reactive protein and training in communication skills on antibiotic use in lower respiratory tract infections: cluster randomised trial

Abstract: Objective To assess the effect of general practitioner testing for C reactive protein (disease approach) and receiving training in enhanced communication skills (illness approach) on antibiotic prescribing for lower respiratory tract infection.Design Pragmatic, 2×2 factorial, cluster randomised controlled trial.Setting 20 general practices in the Netherlands.Participants 40 general practitioners from 20 practices recruited 431 patients with lower respiratory tract infection.Main outcome measures The primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
446
5
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(471 citation statements)
references
References 52 publications
(68 reference statements)
12
446
5
8
Order By: Relevance
“…A previous study indicated that point-of-care testing for CRP in lower respiratory tract infections in primary care significantly reduced antimicrobial prescribing without compromising patient recovery [26]. However, the patients had mild disease and a mean age of 50 yrs, and only 7% had a diagnosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that point-of-care testing for CRP in lower respiratory tract infections in primary care significantly reduced antimicrobial prescribing without compromising patient recovery [26]. However, the patients had mild disease and a mean age of 50 yrs, and only 7% had a diagnosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Acute cough is one of the commonest reasons for seeking health care, and although studies have shown little or no benefit from antibiotic treatment in otherwise well people [18][19][20] , patients continue to expect antibiotics and clinicians continue to prescribe them for this condition. 5,17,21,22 Practitioners are generally aware that high rates of antibiotic prescribing are associated with increasing antibiotic resistance but continue to prescribe antibiotics for respiratory tract infections 23 , often due to a balancing act between what is 'clinically best' against perceived patient expectations 24 and a sense of social responsibility. 25 We therefore aimed to explore the consistency in patients' interpretation of the term 'antibiotic resistance' across a wider cross-section of European settings and to consider the implications for interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] However, they have generally been designed for implementation in a single context 6,7 and have focused on a single country, health care organisation and culture.…”
Section: Introductionmentioning
confidence: 99%